EFFECT OF ORGANIC AND INORGANIC FERTILIZER ON AVAILABILITY OF POTASSIUM IN SOIL AND YIELD OF CHICKPEA (Cicer arietinum L.). - S. Y. Akrawi, H. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2019)
A field experiments was conducted to evaluate the effect of soil amendments with organic and inorganic fertilizer (chemical fertilizer) on the potassium availability, improve growth and yield of chickpea (Cicer arietinum L). In this experiment each organic and inorganic fertilizer (NPK 15: 15: 15) was added as amount equivalent to potassium (K) at levels 0, 12.5, 25, 50, 100 kg K ha-1. Results revealed that there were significant effect of application organic and inorganic fertilizer on soluble and exchangeable K in soils, the application of organic and inorganic fertilizer at level of 100 kg K ha-1 increased the soluble K from 4.1mg L-1 to 7.99 and 6.00 mg L-1 respectively while, the exchangeable K increase from 23.46 mg kg-1 soil to 118.47 and 74.29 mg kg -1 soil respectively. The uses of the previous treatments were also effective to gain higher yield of chickpea. Application of 100 kg K ha-1 in both organic and inorganic fertilizer gave significantly the highest value. The highest biological yield (2537.78 and 2422.22 kg ha-1) was obtained when the soil amended with 100 kg K ha-1 organic matter and inorganic fertilizer respectively.